Simultaneous measurement of multiple independent atomic-scale interactions using scanning probe microscopy: Data interpretation and the effect of cross-talk - Baykara, M.Z.; Todorović, M.; Mönig, H.; Schwendemann, T.C.; Rodrigo, L.; Altman, E.I.; Pérez, R.; Schwarz, U.D. (Journal of Physical Chemistry C, 2015)
In high-resolution scanning probe microscopy, it is becoming increasingly common to simultaneously record multiple channels representing different tip-sample interactions to collect complementary information about the sample surface. A popular choice involves simultaneous scanning tunneling microscopy (STM) and noncontact atomic force microscopy (NC-AFM) measurements, which are thought to reflect the chemical and electronic properties of the sample surface. With surface-oxidized Cu(100) as an example, we investigate whether atomic-scale information on chemical interactions can be reliably extracted from frequency shift maps obtained while using the tunneling current as the feedback parameter. Ab initio calculations of interaction forces between specific tip apexes and the surface are utilized to compare experiments with theoretical expectations. The examination reveals that constant-current operation may induce a noticeable influence of topography-feedback-induced cross-talk on the frequency shift data, resulting in misleading interpretations of local chemical interactions on the surface. Consequently, the need to apply methods such as 3D-AFM is emphasized when accurate conclusions about both the local charge density near the Fermi level, as provided by the STM channel, and the site-specific strength of tip-sample interactions (NC-AFM channel) are desired. We conclude by generalizing to the case where multiple atomic-scale interactions are being probed while only one of them is kept constant. © 2015 American Chemical Society.
8 citations (Crossref) [2023-10-31]
Keywords: Ab initio calculations; Atomic force microscopy; Atomic-scale interaction; Calculations; Chemical interactions; Constant current operations; Crosstalk; Electronic properties; High resolution scanning; Hydrophobicity; Noncontact atomic force microscopy; Scanning tunneling microscopy; Simultaneous measurement; Tip-sample interaction; Topography; dept.phy

Preface - Jain, F.; Broadbridge, C.; Tang, H. (International Journal of High Speed Electronics and Systems, 2015)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Fluctuation-driven selection at criticality in a frustrated magnetic system: the case of multiple-k partial order on the pyrochlore lattice. - Javanparast, Behnam; Hao, Zhihao; Enjalran, Matthew; Gingras, Michel J P (Physical review letters, 2015)
We study the problem of partially ordered phases with periodically arranged disordered (paramagnetic) sites on the pyrochlore lattice, a network of corner-sharing tetrahedra. The periodicity of these phases is characterized by one or more wave vectors k={1/21/21/2}. Starting from a general microscopic Hamiltonian including anisotropic nearest-neighbor exchange, long-range dipolar interactions, and second- and third-nearest neighbor exchange, we use standard mean-field theory (SMFT) to identify an extended range of interaction parameters that support partially ordered phases. We demonstrate that thermal fluctuations ignored in SMFT are responsible for the selection of one particular partially ordered phase, e.g., the "4-k" phase over the "1-k" phase. We suggest that the transition into the 4-k phase is continuous with its critical properties controlled by the cubic fixed point of a Ginzburg-Landau theory with a four-component vector order parameter. By combining an extension of the Thouless-Anderson-Palmer method originally used to study fluctuations in spin glasses with parallel-tempering Monte Carlo simulations, we establish the phase diagram for different types of partially ordered phases. Our results elucidate the long-standing puzzle concerning the origin of the 4-k partially ordered phase observed in the Gd2Ti2O7 dipolar pyrochlore antiferromagnet below its paramagnetic phase transition temperature.
21 citations (Crossref) [2023-10-31] Place: United States Javanparast, Behnam. Department of Physics and Astronomy, University of Waterloo, Waterloo, Ontario N2L 3G1, Canada. Hao, Zhihao. Department of Physics and Astronomy, University of Waterloo, Waterloo, Ontario N2L 3G1, Canada. Enjalran, Matthew. Physics Department, Southern Connecticut State University, 501 Crescent Street, New Haven, Connecticut 06515-1355, USA. Gingras, Michel J P. Department of Physics and Astronomy, University of Waterloo, Waterloo, Ontario N2L 3G1, Canada. Gingras, Michel J P. Canadian Institute for Advanced Research, 180 Dundas Street West, Toronto, Ontario M5G 1Z8, Canada. Gingras, Michel J P. Perimeter Institute for Theoretical Physics, 31 Caroline Street North, Waterloo, Ontario N2L 2Y5, Canada.
Keywords: Corner-sharing tetrahedra; Crystal lattices; Ginzburg Landau theory; Hamiltonians; Intelligent systems; Interaction parameters; Mean field theory; Microscopic hamiltonians; Monte Carlo methods; Parallel tempering Monte Carlo simulations; Paramagnetic phase transitions; Paramagnetism; Phase diagrams; Spin fluctuations; Thermal fluctuations; Vector order parameter; dept.phy

Observations of binary stars with the differential speckle survey instrument. VI. Measures during 2014 at the Discovery Channel Telescope - Horch, Elliott P.; van Belle, Gerard T.; Davidson, James W.; Ciastko, Lindsay A.; Everett, Mark E.; Bjorkman, Karen S. (The Astronomical Journal, 2015)
We present the results of 938 speckle measures of double stars and suspected double stars drawn mainly from the Hipparcos Catalog, as well as 208 observations where no companion was noted. One hundred fourteen pairs have been resolved for the first time. The data were obtained during four observing runs in 2014 using the Differential Speckle Survey Instrument at Lowell Observatory's Discovery Channel Telescope. The measurement precision obtained when comparing to ephemeris positions of binaries with very well-known orbits is generally less than 2 mas in separation and 0.°5 in position angle. Differential photometry is found to have internal precision of approximately 0.1 mag and to be in very good agreement with Hipparcos measures in cases where the comparison is most relevant. We also estimate the detection limit in the cases where no companion was found. Visual orbital elements are derived for six systems. © 2015. The American Astronomical Society. All rights reserved.
53 citations (Crossref) [2023-10-31] Citation Key Alias: pop00059 tex.type: [object Object]
Keywords: astrometry; binaries: visual; dept.phy; peer-reviewed; techniques: interferometric; techniques: photometric

Computational nanocharacterization for combinatorially developed bulk metallic glass - Gossett, Eric; Scanley, Ellen; Liu, Yanhui; Li, Yanglin; Liu, Ze; Sohn, Sungwoo; Schroers, Jan; Broadbridge, Christine; Schwendemann, Todd C. (International Journal of High Speed Electronics and Systems, 2015)
Bulk metallic glasses synthesized at specialized facilities at Yale using magnetron cosputtering are sent to Southern Connecticut State University for elemental characterization. Characterization is done using a Zeiss Sigma VP SEM coupled with an Oxford EDS. Characterization is automated using control software provided by Oxford. Collected data is processed and visualized using computational methods developed internally. Processed data is then organized into a database suitable for web retrieval. This technique allows for the rapid characterization of a combinatorial wafer to be carried out in ~11 hours for a single wafer containing ~600 unique compounds. © 2015 World Scientific Publishing Company.
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00134 tex.type: [object Object]
Keywords: Bulk metallic glass; Combinatorial synthesis; Computational methods; Control software; Glass; Magnetron co-sputtering; Magnetron sputtering; Metallic glass; Nano-characterization; Single wafer; Spectrography; Web retrieval; combinatorial synthesis; computational methods; dept.phy; energy dispersive X-ray spectrography; magnetron sputtering; nano-characterization; peer-reviewed

Combinatorial exploration of color in gold-based alloys - Liu, Jingbei; Liu, Yanhui; Gong, Pan; Li, Yanglin; Moore, Kimberly M.; Scanley, Ellen; Walker, Fred; Broadbridge, Christine; Schroers, Jan (Gold Bulletin, 2015)
Combinatorial approaches comprised of combinatorial magnetron co-sputtering deposition and fast screening methods are introduced to study color as a function of composition in Au-based alloys. The microstructures of the thin films and bulk alloys are identified by X-ray diffraction, and their colors of the alloys are characterized by optical reflectivity. The results reveal that when comparing microstructures and reflectivity, thin films are similar to bulk alloys. In Au-Ag-Cu solid solutions, the color of the ternary alloy follows the rule of mixture. For colors resulting from AuAl2 intermetallic, the color of an alloy scales with the percentage of the intermetallic phase and the deviation from its ideal binary composition. In the Au-Al-Cu library, we found a ∼90 % AuAl2 area fraction compositional window where copper addition can be tuned to improve mechanical properties while keeping purple color, even though Al and CuAl2 phases exist. Moreover, when comparing the color in Au-Cu-Si-Ag amorphous and crystalline state solid solution for the same composition, the colors are essentially identical. © 2015 The Author(s).
32 citations (Crossref) [2023-10-31] Citation Key Alias: pop00036 tex.type: [object Object]
Keywords: Aluminum; Amorphous alloys; Amorphous silicon; Amorphousalloys; Binary composition; Color; Combinatorial approach; Crystalline materials; Crystalline state; Decorative thin film coating; Decorative thin films; Gold; Gold alloys; Gold based alloys; Gold coatings; Intermetallic phase; Intermetallics; Magnetron co-sputtering; Magnetrons; Microstructure; Optical reflectivity; Reflection; Silver; Silver alloys; Solid solution; Solid solutions; Thin films; X ray diffraction; dept.phy

Influence of stellar multiplicity on planet formation. III. adaptive optics imaging of kepler stars with gas giant planets - Wang, Ji; Fischer, Debra A.; Horch, Elliott P.; Xie, Ji-Wei (The Astrophysical Journal, 2015)
As hundreds of gas giant planets have been discovered, we study how these planets form and evolve in different stellar environments, specifically in multiple stellar systems. In such systems, stellar companions may have a profound influence on gas giant planet formation and evolution via several dynamical effects such as truncation and perturbation. We select 84 Kepler Objects of Interest (KOIs) with gas giant planet candidates. We obtain high-angular resolution images using telescopes with adaptive optics (AO) systems. Together with the AO data, we use archival radial velocity data and dynamical analysis to constrain the presence of stellar companions. We detect 59 stellar companions around 40 KOIs for which we develop methods of testing their physical association. These methods are based on color information and galactic stellar population statistics. We find evidence of suppressive planet formation within 20 AU by comparing stellar multiplicity. The stellar multiplicity rate (MR) for planet host stars is 0+5-0% within 20 AU. In comparison, the stellar MR is 18% ± 2% for the control sample, i.e., field stars in the solar neighborhood. The stellar MR for planet host stars is 34% ± 8% for separations between 20 and 200 AU, which is higher than the control sample at 12% ± 2%. Beyond 200 AU, stellar MRs are comparable between planet host stars and the control sample. We discuss the implications of the results on gas giant planet formation and evolution. © 2015. The American Astronomical Society. All rights reserved.
59 citations (Crossref) [2023-10-31] Citation Key Alias: pop00037 tex.type: [object Object]
Keywords: dept.phy; methods: observational; methods: statistical; planet-star interactions; planetary systems; planets and satellites: formation; techniques: high angular resolution

Oxide 2D electron gases as a route for high carrier densities on (001) Si - Kornblum, Lior; Jin, Eric N.; Kumah, Divine; Ernst, Alexis T.; Broadbridge, Christine; Ahn, Chong H.; Walker, Fred (Applied Physics Letters, 2015)
Two dimensional electron gases (2DEGs) formed at the interfaces of oxide heterostructures draw considerable interest owing to their unique physics and potential applications. Growing such heterostructures on conventional semiconductors has the potential to integrate their functionality with semiconductor device technology. We demonstrate 2DEGs on a conventional semiconductor by growing GdTiO3-SrTiO3 on silicon. Structural analysis confirms the epitaxial growth of heterostructures with abrupt interfaces and a high degree of crystallinity. Transport measurements show the conduction to be an interface effect, ∼9 × 1013 cm-2 electrons per interface. Good agreement is demonstrated between the electronic behavior of structures grown on Si and on an oxide substrate, validating the robustness of this approach to bridge between lab-scale samples to a scalable, technologically relevant materials system. © 2015 AIP Publishing LLC.
16 citations (Crossref) [2023-10-31] Citation Key Alias: pop00055 tex.type: [object Object]
Keywords: D electrons; Degree of crystallinity; Electron gas; Electronic behaviors; Heterojunctions; Interface effect; Materials systems; Oxide heterostructures; Oxide substrates; Semiconducting silicon; Semiconductor devices; Silicon; Transport measurements; Two dimensional electron gas; dept.phy

A seismic and gravitationally bound double star observed by Kepler - Appourchaux, T; Antia, H M; Ball, Warrick H; Creevey, O; Lebreton, Y; Verma, Kuldeep; Vorontsov, Sergei V; Campante, T L; Campante, T L; Davies, G R; Davies, G R; Gaulme, Patrick; et al. (Astronomy and Astrophysics, 2015)
Context. Solar-like oscillations have been observed by Kepler and CoRoT in many solar-type stars, thereby providing a way to probe stars using asteroseismology. Aims. The derivation of stellar parameters has usually been done with single stars. The aim of the paper is to derive the stellar parameters of a double-star system (HIP93511), for which an interferometric orbit has been observed along with asteroseismic measurements. Methods. We used a time series of nearly two years of data for the double star to detect the two oscillation-mode envelopes that appear in the power spectrum. Using a new scaling relation based on luminosity, we derived the radius and mass of each star. We derived the age of each star using two proxies: one based upon the large frequency separation and a new one based upon the small frequency separation. Using stellar modelling, the mode frequencies allowed us to derive the radius, the mass, and the age of each component. In addition, speckle interferometry performed since 2006 has enabled us to recover the orbit of the system and the total mass of the system. Results. From the determination of the orbit, the total mass of the system is 2.34-0.33 +0.45 M⊙. The total seismic mass using scaling relations is 2.47 ± 0.07 M⊙. The seismic age derived using the new proxy based upon the small frequency separation is 3.5 ± 0.3 Gyr. Based on stellar modelling, the mean common age of the system is 2.7-3.9 Gyr. The mean total seismic mass of the system is 2.34-2.53 M⊙ consistent with what we determined independently with the orbit. The stellar models provide the mean radius, mass, and age of the stars as RA = 1.82-1.87R⊙, MA = 1.25-1.39 M⊙, AgeA = 2.6-3.5 Gyr; RB = 1.22-1.25 R⊙, MB = 1.08-1.14 M⊙, AgeB = 3.35-4.21 Gyr. The models provide two sets of values for Star A: [1.25-1.27] M⊙ and [1.34-1.39] M⊙. We detect a convective core in Star A, while Star B does not have any. For the metallicity of the binary system of Z ≈ 0.02, we set the limit between stars having a convective core in the range [1.14-1.25] M⊙. © ESO, 2015.
42 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-480-656-795-885 tex.type: [object Object]
Keywords: Asteroseismology; Binaries: general; Interferometry; Orbits; Seismology; Separation; Speckle; Stars; Stars: evolution; Stars: solar types; asteroseismology; astrometry; binaries: general; dept.phy; stars: evolution; stars: solar-type

A kinematically-distinct RR-Lyrae overdensity in the inner regions of the milky way - Casetti-Dinescu, Dana I; Nusdeo, Daniel A; Girard, Terrence M; Korchagin, V I; Altena, William F Van (The Astrophysical Journal, 2015)
We combine the Siding Spring Survey of RR Lyrae stars with the Southern Proper Motion Catalog 4, in order to detect and kinematically characterize overdensities in the inner halo of the Milky Way. We identify one such overdensity above the Galactic plane, in quadrant 4 of the Galaxy. The overdensity extends at least 20° in longitude, has an average heliocentric distance of 8 kpc with a depth of 4 kpc, and is confined within 4 kpc of the Galactic plane. Its metallicity distribution is distinct from that of the field population having a peak at -1.3 and a pronounced tail to -2.0. Proper motions indicate a net vertical motion away from the plane, and a low orbital angular momentum. Qualitatively, these orbit properties suggest a possible association with ω Centauri's parent satellite. However, comparison to a specific ω Cen N-body disruption model does not give a good match with observations. Line of sight velocities, and more extensive N-body modeling will help clarify the nature of this overdensity. © 2015. The American Astronomical Society. All rights reserved.
Citation Key Alias: lens.org/124-540-032-308-91X tex.type: [object Object]
Keywords: Galaxy: halo; Galaxy: kinematics and dynamics; dept.phy; stars: variables: RR Lyrae; ⚠️ Invalid DOI

Understanding the effects of stellar multiplicity on the derived planet radii from transit surveys: implications for kepler, k2, and TESS - Ciardi, David R; Beichman, Charles A; Horch, Elliott P; Howell, Steve B (The Astrophysical Journal, 2015)
We present a study on the effect of undetected stellar companions on the derived planetary radii for Kepler Objects of Interest (KOIs). The current production of the KOI list assumes that each KOI is a single star. Not accounting for stellar multiplicity statistically biases the planets toward smaller radii. The bias toward smaller radii depends on the properties of the companion stars and whether the planets orbit the primary or the companion stars. Defining a planetary radius correction factor, XR, we find that if the KOIs are assumed to be single, then, on average, the planetary radii may be underestimated by a factor of 〈XR〉 ≈ 1.5. If typical radial velocity and high-resolution imaging observations are performed and no companions are detected, then this factor reduces to 〈XR〉 ≈ 1.2. The correction factor 〈XR〉 is dependent on the primary star properties and ranges from 〈XR〉 ≈ 1.6 for A and F stars to 〈XR〉 ≈ 1.2 for K and M stars. For missions like K2 and TESS where the stars may be closer than the stars in the Kepler target sample, observational vetting (primary imaging) reduces the radius correction factor to 〈XR〉 ≈ 1.1. Finally, we show that if the stellar multiplicity rates are not accounted for correctly, then occurrence rate calculations for Earth-sized planets may overestimate the frequency of small planets by as much as 15%-20%. © 2015. The American Astronomical Society. All rights reserved.
182 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/088-016-640-995-341 tex.type: [object Object]
Keywords: binaries: general; dept.phy; planetary systems

Patterned deposition of nanoparticles using dip pen nanolithography for synthesis of carbon nanotubes - Dahlberg, Kevin; Woods, Kelly; Jenkins, Carol; Broadbridge, Christine; Schwendemann, Todd C (MRS Proceedings, 2015)
Ordered carbon nanotube (CNT) growth by deposition of nanoparticle catalysts using dip pen nanolithography (DPN) is presented. DPN is a direct write, tip based lithography technique capable of multi-component deposition of a wide range of materials with nanometer precision. A Nanolnk NLP 2000 is used to pattern different catalytic nanoparticle solutions on various substrates. To generate a uniform pattern of nanoparticle clusters, various conditions need to be considered. These parameters include: the humidity in the vessel, temperature, and tip-surface dwell time. By patterning different nanoparticle solutions next to each other, identical growth conditions can be compared for different catalysts in a streamlined analysis process. Fe, Ni, and Co nanoparticle solutions patterned on silicon, mica, and graphite substrates serve as nucleation sites for CNT growth. The CNTs were synthesized by a chemical vapor deposition (CVD) reaction. Each nanoparticle patterned substrate is placed in a tube furnace held at 725°C during CNT growth. The carbon source used in the growth chamber is toluene. The toluene is injected at a rate of 5 mL/hr. Growth is observed for Fe and Ni nanoparticle patterns, but is lacking for the Co patterns. The results of these reactions provide important information regarding efficient and highly reproducible mechanisms for CNT growth. © 2015 Materials Research Society.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/070-622-015-549-684 tex.type: [object Object]
Keywords: Carbon nanotubes; Catalysts; Catalytic nanoparticle; Chemical vapor deposition; Chemical vapor depositions (CVD); Deposition; Dip-pen nanolithography; Lithography; Mica; Nanolithography; Nanoparticle catalysts; Nanoparticle clusters; Nanoparticle solutions; Nanoparticles; Nanotubes; Nickel; Patterned deposition; Patterned substrates; Silicate minerals; Substrates; Synthesis (chemical); Toluene; Vapor deposition; Yarn; dept.phy

High-resolution multi-band imaging for validation and characterization of small kepler planets - Everett, Mark E.; Barclay, Thomas; Ciardi, David R.; Horch, Elliott P.; Howell, Steve B.; Crepp, Justin R.; Silva, David R. (The Astronomical Journal, 2015)
High-resolution ground-based optical speckle and near-infrared adaptive optics images are taken to search for stars in close angular proximity to host stars of candidate planets identi fied by the NASA Kepler Mission. Neighboring stars are a potential source of false positive signals. These stars also blend into Kepler light curves, affecting estimated planet properties, and are important for an understanding of planets in multiple star systems. Deep images with high angular resolution help to validate candidate planets by excluding potential background eclipsing binaries as the source of the transit signals. A study of 18 Kepler Object of Interest stars hosting a total of 28 candidate and validated planets is presented. Validation levels are determined for 18 planets against the likelihood of a false positive from a background eclipsing binary. Most of these are validated at the 99% level or higher, including five newly validated planets in two systems: Kepler-430 and Kepler-431. The stellar properties of the candidate host stars are determined by supplementing existing literature values with new spectroscopic characterizations. Close neighbors of seven of these stars are examined using multi-wavelength photometry to determine their nature and influence on the candidate planet properties. Most of the close neighbors appear to be gravitationally bound secondaries, while a few are best explained as closely co-aligned field stars. Revised planet properties are derived for each candidate and validated planet, including cases where the close neighbors are the potential host stars. © 2015. The American Astronomical Society. All rights reserved.
46 citations (Crossref) [2023-10-31] Citation Key Alias: pop00061 tex.type: [object Object]
Keywords: Binaries: visual; Planetary systems; Planets and satellites: detection; Planets and satellites: fundamental parameters; Surveys; Techniques: high angular resolution; dept.phy; peer-reviewed

Research Experiences for Students: Interdisciplinary skill development to prepare the future workforce for success - Ferrari, Nicole; Jenkins, Carol; Garofano, Jacquelynn; Day, Deborah A; Schwendemann, Todd C; Broadbridge, Christine (MRS Proceedings, 2015)
Research Experiences for Undergraduates (REU) programs traditionally function as a recruitment vehicle to encourage students to pursue further studies in STEM (Science, Technology, Engineering and Math) and as an opportunity for STEM majors to delve deeper into their chosen fields of study. Based on a critical examination of REU student feedback, evaluators at CRISP (Center for Research on Interface Structures and Phenomena) have found that in addition to these conventional benefits of research-based experiences, the value of interdisciplinary skill development is integral to the REU experience and these contributions may warrant a more formal evaluative definition. Using the emerging 21st Century Skills Framework, CRISP has begun conducting a series of small-scale studies in an effort to define the contribution of student research experiences in cross-disciplinary skill development and the positive effects that exposure to real-world science practices have on refinement of career decisions and vocational success. Using Likert-type survey methods, this study directly examines current and former REU students' perceptions of the importance of interdisciplinary 21st century skills such as creativity, collaboration, communication, information literacy, and problem-solving in their REU experience and their perceived value of these skills in their future and/or current careers. Through better understanding the role these "soft skills" play in student research experiences, CRISP hopes to maximize these interdisciplinary benefits within its REU program to best prepare students for the complex demands of the 21st century workplace. © 2015 Materials Research Society.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/096-003-001-017-805 tex.type: [object Object]
Keywords: Amphibious vehicles; Cross-disciplinary; Education; Engineering research; Functions; Information literacy; Interdisciplinary skills; Interface structures; Problem solving; Research Experiences for Undergraduates programs; Research experiences for students; Research-based experiences; Skill development; Students; dept.phy

Cutting the cord: toward wireless optical intensity interferometry - Horch, Elliott P (Proceedings of SPIE, 2015)
Intensity interferometry, which was first used for obtaining ultra-high-resolution image information in astronomy in the 1960's and 1970's, is now being revived using modern detectors and electronics. This paper explores the possibility of wireless optical interferometry made possible by technological advancements in timing correlation, signal processing, and detector technology. If this can be achieved, then baselines of one to several kilometers may be possible in optical interferometry in the coming years. This would improve the resolution over the current generation of amplitude-based optical interferometers by a factor of at least ten. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only. © 2015 SPIE.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/068-868-231-716-094 tex.type: [object Object]
Keywords: Avalanche diodes; Correlation detectors; Current generation; Detector technology; Interferometry; Optical correlation; Optical interferometer; Optical interferometry; Particle beams; Photon counting; Photons; Signal processing; Single photon avalanche diode; Single photon avalanche diodes; Technological advancement; Timing correlation; Ultra-high-resolution astronomy; Ultrahigh resolution; dept.phy

Observations of binary stars with the differential speckle survey instrument. V. toward an empirical metal-poor mass–luminosity relation - Horch, Elliott P; Altena, William F Van; Demarque, Pierre; Howell, Steve B; Everett, Mark E; Ciardi, David R; Teske, Johanna K; Henry, Todd J; Winters, Jennifer G (The Astronomical Journal, 2015)
In an effort to better understand the details of the stellar structure and evolution of metal-poor stars, the Gemini North telescope was used on two occasions to take speckle imaging data of a sample of known spectroscopic binary stars and other nearby stars in order to search for and resolve close companions. The observations were obtained using the Differential Speckle Survey Instrument, which takes data in two filters simultaneously. The results presented here are of 90 observations of 23 systems in which one or more companions was detected, and six stars where no companion was detected to the limit of the camera capabilities at Gemini. In the case of the binary and multiple stars, these results are then further analyzed to make first orbit determinations in five cases, and orbit refinements in four other cases. The mass information is derived, and since the systems span a range in metallicity, a study is presented that compares our results with the expected trend in total mass as derived from the most recent Yale isochrones as a function of metal abundance. These data suggest that metal-poor main-sequence stars are less massive at a given color than their solar-metallicity analogues in a manner consistent with that predicted from the theory. © 2015. The American Astronomical Society. All rights reserved..
25 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-359-698-007-676 tex.type: [object Object]
Keywords: astrometry; binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Dynamical masses of young M dwarfs: masses and orbital parameters of gj 3305 ab, the wide binary companion to the imaged exoplanet host 51 eri - Montet, Benjamin T; Bowler, Brendan P; Shkolnik, Evgenya L; Deck, Katherine M; Wang, Ji; Horch, Elliott P; Liu, Michael C; Hillenbrand, Lynne A; Kraus, Adam L; Charbonneau, David; Hillenbrand, Lynne A; Kraus, Adam L; et al. (The Astrophysical Journal, 2015)
We combine new high resolution imaging and spectroscopy from Keck/NIRC2, Discovery Channel Telescope/DSSI, and Keck/HIRES with published astrometry and radial velocities to measure individual masses and orbital elements of the GJ 3305 AB system, a young (∼20 Myr) M+M binary (unresolved spectral type M0) member of the β Pictoris moving group comoving with the imaged exoplanet host 51 Eri. We measure a total system mass of 1.11 ± 0.04 , a period of 29.03 ± 0.50 year, a semimajor axis of 9.78 ± 0.14 AU, and an eccentricity of 0.19 ± 0.02. The primary component has a dynamical mass of 0.67 ± 0.05 and the secondary has a mass of 0.44 ± 0.05 . The recently updated BHAC15 models are consistent with the masses of both stars to within Given the observed masses the models predict an age of the GJ 3305 AB system of 37 ± 9 Myr. Based on the observed system architecture and our dynamical mass measurement, it is unlikely that the orbit of 51 Eri b has been significantly altered by the Kozai-Lidov mechanism. © 2015. The American Astronomical Society. All rights reserved..
42 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/082-123-910-981-94X tex.type: [object Object]
Keywords: astrometry; binaries: close; dept.phy; stars: fundamental parameters; stars: individual (GJ 3305 AB)

A comparison of spectroscopic versus imaging techniques for detecting close companions to kepler objects of interest - Teske, Johanna K; Everett, Mark E; Hirsch, Lea A; Furlan, Elise; Horch, Elliott P; Horch, Elliott P; Howell, Steve B; Ciardi, David R; Gonzales, Erica J; Crepp, Justin R (The Astronomical Journal, 2015)
Kepler planet candidates require both spectroscopic and imaging follow-up observations to rule out false positives and detect blended stars. Traditionally, spectroscopy and high-resolution imaging have probed different host star companion parameter spaces, the former detecting tight binaries and the latter detecting wider bound companions as well as chance background stars. In this paper, we examine a sample of 11 Kepler host stars with companions detected by two techniques - near-infrared adaptive optics and/or optical speckle interferometry imaging, and a new spectroscopic deblending method. We compare the companion effective temperatures (Teff) and flux ratios (FB/FA, where A is the primary and B is the companion) derived from each technique and find no cases where both companion parameters agree within 1σ errors. In 3/11 cases the companion Teff values agree within 1σ errors, and in 2/11 cases the companion FB/FA values agree within 1σ errors. Examining each Kepler system individually considering multiple avenues (isochrone mapping, contrast curves, probability of being bound), we suggest two cases for which the techniques most likely agree in their companion detections (detect the same companion star). Overall, our results support the advantage that the spectroscopic deblending technique has for finding very close-in companions (θ ≲ 0.″02-0.″05) that are not easily detectable with imaging. However, we also specifically show how high-contrast AO and speckle imaging observations detect companions at larger separations (θ ≥ 0.″02-0.″05) that are missed by the spectroscopic technique, provide additional information for characterizing the companion and its potential contamination (e.g., position angle, separation, magnitude differences), and cover a wider range of primary star effective temperatures. The investigation presented here illustrates the utility of combining the two techniques to reveal higher-order multiples in known planet-hosting systems. © 2015. The American Astronomical Society. All rights reserved.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/163-960-215-288-558 tex.type: [object Object]
Keywords: binaries: general; dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution; techniques: interferometric; techniques: photometric; techniques: spectroscopic

Speckle interferometry at soar in 2014 - Tokovinin, Andrei; Mason, Brian D; Hartkopf, William I; Mendez, Rene A; Horch, Elliott P (The Astronomical Journal, 2015)
The results of speckle interferometric observations at the Southern Astrophysical Research Telescope (SOAR) telescope in 2014 are given. A total of 1641 observations were taken, yielding 1636 measurements of 1218 resolved binary and multiple stars and 577 non-resolutions of 441 targets. We resolved for the first time 56 pairs, including some nearby astrometric or spectroscopic binaries and ten new subsystems in previously known visual binaries. The calibration of the data is checked by linear fits to the positions of 41 wide binaries observed at SOAR over several seasons. The typical calibration accuracy is 0.°1 in angle and 0.3% in pixel scale, while the measurement errors are on the order of 3 mas. The new data are used here to compute 194 binary star orbits, 148 of which are improvements on previous orbital solutions and 46 are first-time orbits. © 2015. The American Astronomical Society. All rights reserved..
81 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-545-424-948-585 tex.type: [object Object]
Keywords: binaries: general; dept.phy; peer-reviewed

Validation of 12 small kepler transiting planets in the habitable zone - Torres, Guillermo; Kipping, David M; Fressin, Francois; Caldwell, Douglas A; Twicken, Joseph D; Ballard, Sarah; Batalha, Natalie M; Bryson, Stephen T; Ciardi, David R; Henze, Christopher E; Howell, Steve B; Isaacson, Howard; et al. (The Astrophysical Journal, 2015)
We present an investigation of 12 candidate transiting planets from Kepler with orbital periods ranging from 34 to 207 days, selected from initial indications that they are small and potentially in the habitable zone (HZ) of their parent stars. Few of these objects are known. The expected Doppler signals are too small to confirm them by demonstrating that their masses are in the planetary regime. Here we verify their planetary nature by validating them statistically using the BLENDER technique, which simulates large numbers of false positives and compares the resulting light curves with the Kepler photometry. This analysis was supplemented with new follow-up observations (high-resolution optical and near-infrared spectroscopy, adaptive optics imaging, and speckle interferometry), as well as an analysis of the flux centroids. For 11 of them (KOI-0571.05, 1422.04, 1422.05, 2529.02, 3255.01, 3284.01, 4005.01, 4087.01, 4622.01, 4742.01, and 4745.01) we show that the likelihood they are true planets is far greater than that of a false positive, to a confidence level of 99.73% (3σ) or higher. For KOI-4427.01 the confidence level is about 99.2% (2.6σ). With our accurate characterization of the GKM host stars, the derived planetary radii range from 1.1 to 2.7 R ⊕. All 12 objects are confirmed to be in the HZ, and nine are small enough to be rocky. Excluding three of them that have been previously validated by others, our study doubles the number of known rocky planets in the HZ. KOI-3284.01 (Kepler-438b) and KOI-4742.01 (Kepler-442b) are the planets most similar to the Earth discovered to date when considering their size and incident flux jointly. © 2015. The American Astronomical Society. All rights reserved..
94 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/036-512-292-095-617 tex.type: [object Object]
Keywords: dept.phy; methods: statistical; planetary systems; stars: individual (KOI-3284 (Kepler-438); KOI-4742 (Kepler-442)); techniques: photometric

On the occurrence rate of hot jupiters in different stellar environments - Wang, Ji; Fischer, Debra A; Horch, Elliott P; Huang, Xu (The Astrophysical Journal, 2015)
Many hot Jupiters (HJs) are detected by the Doppler and transit techniques. From surveys using these two techniques, however, the measured HJ occurrence rates differ by a factor of two or more. Using the California Planet Survey sample and the Kepler sample, we investigate the causes for this difference in the HJ occurrence rate. First, we find that 12.8% ± 0.24% of HJs are misidentified in the Kepler mission because of photometric dilution and subgiant contamination. Second, we explore the differences between the Doppler sample and the Kepler sample that can account for the different HJ occurrence rate. Third, we discuss how to measure the fundamental HJ occurrence rates by synthesizing the results from the Doppler and Kepler surveys. The fundamental HJ occurrence rates are measures of the HJ occurrence rate as a function of stellar multiplicity and evolutionary stage, e.g., the HJ occurrence rate for single and multiple stars or for main-sequence and subgiant stars. While we find qualitative evidence that HJs occur less frequently in subgiants and multiple stellar systems, we conclude that our current knowledge of stellar properties and the stellar multiplicity rate is too limited for us to reach any quantitative result for the fundamental HJ occurrence rates. This concern extends to ηEarth, the occurrence rate of Earth-like planets. © 2015. The American Astronomical Society. All rights reserved.
54 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/156-890-481-368-476 tex.type: [object Object]
Keywords: Fundamental parameters stars; Methods; Photometric techniques; Radial velocities; Solar-type stars; Statistical planets and satellites; Statistics techniques; dept.phy